Effect of dietary supplementation of rice dried distillers’ grain on nutrient utilization and blood biochemical profile in Osmanabadi kids - SINGH, SUKHVEER; DUBEY, MEENU; PRUSTY, SONALI; GADPAYLE, RAJKUMAR; DONERIA, RAINA (The Indian Journal of Animal Sciences, 2021)
A study on 15 Osmanabadi kids (4-5 months old) was conducted for 90 days to find out the effect of dietary inclusion of rice dried distillers grain with solubles (RDGS) on growth performance, nutrient utilization and blood biochemical parameters. They were divided randomly into 3 groups T1, T2 and T3. In the concentrate mixture, RDGS was included at 0% (T1), 10% (T2) and 20% (T3) levels replacing soybean meal. There was higher average daily gain in T3 compared to control (T1), however, the variation was non-significant up to 75 days. During last fortnight (75-90 d) the ADG was significantly higher in group T3 than T1. There was no significant effect of dietary inclusion of RDGS on percentage DMI and digestibility of nutrients, however from 75 to 90 days, DMI (kg/W0.75) was significantly (P<0.05) higher in T3 compared to T1 and T2. The effect of dietary RDGS on serum biochemical parameters, viz. total protein, albumin, globulin (g/dl) and A: G ratio was non-significant. Inclusion of RDGS reduced the cholesterol content, however, the difference was nonsignificant. The feed cost per kg BW weight gain (`) was low in T3 (` 141.06) compared to T1 (````` 161.78) and T2 (` 160.34). RDGS inclusion up to 20% of DM in the concentrate feed replacing soybean meal improved the economy of goat rearing without affecting growth performance, nutrient digestibility and blood biochemical parameters of Osmanabadi goats.